2019
DOI: 10.1097/mph.0000000000001162
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Severe Iron Deficiency Anemia and Thrombocytopenia in an Adolescent Male

Abstract: An adolescent male presented with recurrent episodes over several years of severe iron deficiency anemia and associated severe thrombocytopenia. The anemia was secondary to chronic blood loss due to ulceration at the site of an ileocolonic anastomosis performed during infancy. We were able to demonstrate complete resolution of thrombocytopenia with the administration of iron, and without using steroids, intravenous immunoglobulin, or platelet transfusions. This is the first reported case of an individual with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…HIV-related thrombocytopenia has been reported to cause excessive bleeding among females during pregnancy 49. Thus, thrombocytopenia could further increase the risk of anaemia and even aggravate anaemia owing to acute or chronic blood loss among PLHIV 3 50. In addition, this study found that hepatitis C was associated with an increased risk of severe anaemia, which could be explained by the significant side effects of therapy for hepatitis C 51…”
Section: Discussionmentioning
confidence: 76%
“…HIV-related thrombocytopenia has been reported to cause excessive bleeding among females during pregnancy 49. Thus, thrombocytopenia could further increase the risk of anaemia and even aggravate anaemia owing to acute or chronic blood loss among PLHIV 3 50. In addition, this study found that hepatitis C was associated with an increased risk of severe anaemia, which could be explained by the significant side effects of therapy for hepatitis C 51…”
Section: Discussionmentioning
confidence: 76%
“…A total of 11 individual case reports and one case series (containing 9 patients) were found, which are summarized in Tables 1-4 [9][10][11][12][13][14][15][16][17][18][19]. The age of the patients in the study ranged between 15 and 42 years, and a female predominance was observed (a female-to-male ratio of approximately 3:1) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Patient ethnicity Giordano et al [9] 2019 Male 16 African Bayhan et al [10] 2016 Female 15 NA Kahraman et al [11] 2016 Male 17 NA Cunha et al [12] 2015 Female 16 NA Lindgren et al [13] 2009 Male NA NA Ganti et al [14] 2007 Female 39 African American Taskapan et al [15] 2003 Female 37 NA Go et al [16] 2000 Female 30 NA Soff and Levin (case 1) [17] 1988 Female 17 NA Soff and Levin (case 2) [17] 1988 Female 17 NA Knizley et al [18] 1972 Male 42 Black Lioger et al (series) [19] 2016 1 male, 8 females NA NA Platelet at baseline Lowest platelet count Days to nadir Last platelet count Giordano et al [9] 40 k/μL 28 k/μL 5 169 k/μL Bayhan et al [10] 820 x 10 9 /L 48 x 10 9 /L 363 x 10 9 /L Kahraman et al [11] 340 x 10 3 /mcL 68 x 10 3 /mcL 7 159 x 10 3 /mcL Cunha et al [12] 424 x 10 9 /L 45 x 10 9 /L 8 666 x 10 9 /L Lindgren et al [13] NA NA NA NA Ganti et al [14] 127 x 10 3 /mcL 39 x 10 3 /mcL 2 181 x 10 3 /mcL Taskapan et al [15] 102,000/L 2,000/L 8 87,000/L Go et al [16] 426 x 10 9 /L 20 x 10 9 /L 8 NA Soff and Levin (case 1) [17] 168,000/mm 3 21,000/mm 3 6 683,000/mm 3 Soff and Levin (case 2) [17] 717,000/mm 3 105,000/mm 3 10 NA Knizley et al [18] 1,465,000/mm 3 37,000/mm 3 13 265,000/mm 3 Lioger et al (series) [19] 172 ± 133 x 10 9 /L (range: 102-434) 85% from baseline NA…”
Section: No Authors Year Of Publication Patient Gender Patient Age (Ymentioning
confidence: 99%
“…Five cases of iron deficiency anemia and thrombocytopenia reported in this article discussed and reported 6,[8][9][10][11][12][13][14][15][16][17][18] in Table 1 all presented with severe IDA (median 4.5 g/dL, range 1.6-6.9 g/dL) and thrombocytopenia (median 38Â10E9/L, range 7-100Â10E9/L), both improving with iron treatment, which makes another cause such as Idiopathic Thrombocytopenic Purpura unlikely. There is no relationship between the severity of the anemia and the severity of the thrombocytopenia.…”
Section: Resultsmentioning
confidence: 80%
“…A peak of the reticulocyte and the platelet count was seen around day 5 after parenteral iron treatment, while the reticulocyte count peaked around day 9 and the platelet count peaked around day 20 of oral iron treatment. 7 The patients discussed and reported 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 in Table 1 all presented with severe IDA (median 4.5 g/dL, range 1.6‐6.9 g/dL) and thrombocytopenia (median 38×10E9/L, range 7‐100×10E9/L), both improving with iron treatment, which makes another cause such as Idiopathic Thrombocytopenic Purpura unlikely. There is no relationship between the severity of the anemia and the severity of the thrombocytopenia.…”
Section: Resultsmentioning
confidence: 99%